Mood-creativity relationship in groups: The role of equality in idea contribution in temporal mood effects - LEUNG, Angela K. Y. (Institutional Knowledge at Singapore Management University, 2020)
As people working in groups might fare better in solving complex problems than those working alone (e.g., Laughlin, Hatch, Silver, & Boh, Journal of Personality and Social Psychology, 90, 2006 and 644), organizations have increasingly assigned creative projects to groups. Group members contribute their collective efforts over time until the creative project has come to fruition. Although mood is identified as an important antecedent to creativity, little is known about the temporal pattern of how group mood enhances or inhibits group creativity, as well as the underpinning group process that explains the mood—creativity link in groups. We set out to address these questions by taking a within‐group approach to study the temporal trends of how group mood precedes group creativity and to examine idea contribution equality (ICE) as a mediating group process. We conducted a three‐wave longitudinal study among student workgroups tasked to complete a creativity project over a 1‐month span. Evidence showed that positive mood is positively associated with concurrent ICE and negative mood is negatively associated with lagged ICE. Furthermore, a mediation model showed that negative mood eventually hampered expert‐rated group creative performance by reducing ICE over time. These findings add new knowledge to the temporal mood-creativity relation within the group context.